2D Patterned Ion‐Exchange Membranes Induce Electroconvection. Issue 1 (4th November 2018) - Roghmans, Florian; Evdochenko, Elizaveta; Stockmeier, Felix; Schneider, Sven; Smailji, Amel; Tiwari, Rahul; Mikosch, Annabel; Karatay, Elif; Kühne, Alexander; Walther, Andreas; Mani, Ali; Wessling, Matthias
Abstract: Concentration polarization is a diffusion‐limited phenomenon for ion transport in electrodialysis based desalination processes. Once a so‐called limiting current is reached, the resistance of the system rises notably manifested as a plateau region in the current–voltage curves. For long it is hypothesized that altering the surface properties of the membrane can overcome the diffusional transport limitation by the induction of electroconvective vortices mixing the laminar boundary layer. To systematically investigate the influence of geometrical and chemical membrane surface topology on the evolution of electroconvection, circular patterns of polystyrene, poly(2‐vinylpyridine) (P2VP), and P2VP microgels are inkjet printed on cation‐exchange membranes. All types of patterns cause an insignificant increase in membrane resistance but they reduce the plateau lengths indicating the desired accelerated onset of electroconvection. In case of polystyrene (PS) patterns, the drop in plateau length results in a small reduction in transport resistance for overlimiting currents. However, membranes modified with linear P2VP and P2VP microgel patterns do exhibit a significantly decreased resistance in this region at a simultaneous increase of the limiting current density. Direct numerical simulations support the interpretation that the surface charge of the printed patterns influences the direction of the vortices being advantageous during ion transport toward the membrane. Abstract : 2D polymer patterns are ink‐jet printed on Nafion cation‐exchange membranes to enhance electroosmotic fluid instabilities at polarized membrane surfaces. Topological and charge heterogeneities introduced by the polymer patterns induce electroconvection already at low potentials, with the pattern charge regulating the direction of the vortex as validated by direct numerical simulations.